Syme Amputation: Function, Satisfaction, and Prostheses. Issue 6 (July 2020) - Morrison, Stewart G.; Thomson, Phoebe; Lenze, Ulrich; Donnan, Leo T.
Abstract : Background: Syme amputation (SA) is a term used to describe an amputation at the level of the ankle joint in which the heel pad is preserved. It is performed for a number of indications in a pediatric population. SA is purported to hold the advantage of allowing weight bearing without a prosthesis. A limb length discrepancy (LLD) is useful for ambulation without a prosthesis but can be restrictive with regards to the fitting of modern prostheses. Methods: A voluntary survey was distributed to persons living with SA. Recruitment occurred through hospital electronic database and electronic advertising. Data collected included baseline demographic information, data pertaining to weight bearing in different environments, as well as 2 validated outcome measures: the Trinity Amputation and Prosthesis Experience Scales-Revised (TAPES-R activity restriction scale) and the Locomotor Capabilities Index-5 (LCI-5). An illustration was designed to allow participants to classify their LLD by zone in relation to their nonamputated limb. Results: At total of 47 persons living with SA participated. The average age at amputation was 3.7 years (range, 0.5 to 14.1 y), and at survey completion 15.8 years (1.7 to 60.3). Five of the described "zones" of LLD were represented. Average LCI-5 score was 52.6. Mean TAPES-R activity restriction scale was 0.59, the lowest mean being achieved by zone E participants, indicating the least restriction. Ability to walk without a prosthesis was lower in those participants over 11 years, when compared with those under, as well as being dependent on the walking environment. Conclusions: Our study found no trend indicating that a very low LLD was functionally optimal, and indeed found participants with a moderate LLD (zone E) to have the least mean restriction with regard to their prosthesis. Our study demonstrates that ambulation without a prosthesis depends on the environment (ie, flooring), and rates decrease significantly into adulthood. Optimal care should not focus simply "preserving length, " but rather functional optimization and length modulation in parallel with a nuanced understanding of actual daily activities and prosthetic options. Level of Evidence: Level III—retrospective comparative study.